A imagem técnica nos processos comunicacionais e a definição do espaço virtual - Iori, Maria Cristina (2012)
Towards the extensive use of the images in the media and its increasing popularity in the digital landscape, this dissertation studies what changes it makes extensive use of the images on communication and modern science. So, we gathered concepts developed by the philosopher Flusser (1920-1991) and dealing with the transmission of visual information in two-dimensional surfaces. The axis of reflection and analysis are the concepts of line and surface, developed by Flusser, and part an analysis of the structure of the media since the 20th century. Flusser's ideas are confronted with the Russian author who lives and writes in the USA Lev Manovich, who also evaluates the media as a code, structure-related technology. The aim is to study thoroughly the structure that now allows the translation of the world on screens and surfaces. In this sense, the question that arises is how the translations made in technical image (according Flusser) can interfere with cognitive processes. In order to study the changes that prints the technical image to human subjectivity, we used the concepts of emerging paradigm on Boaventura dos Santos, and visuality according to Ferrara. The first talks about the possibility of a paradigm change in science from a new representation of concepts. For the author, the key concepts in this analysis are scale, perspective, resolution and signature, according him, still used today to make the limits of representation and objectivity in modern science. In origin, the concepts used by Boaventura Santos perform with phenomena related to visual perception. We demonstrate that in communicative mediation, the technical image interferes with the process of construction and recognition of these concepts. Lucrecia Ferrara used the concept of visuality. According to the author, visuality, while communicative means going beyond the image - would be rather a cognitive matrix, not just visual, it would call in all directions communicative exchanges not yet codified. According to Ferrara, Flusser had worked in the construction of a theory of visuality, where technical image (image surface) would be capable of generate a spatial cognition. Then we tried to use the concepts presented in Ferrara to analyze a phenomenon of communication - namely, the constant use of technical images such as demarcation of territory in the events of Tahrir Square in Cairo, which culminated in the overthrow of the Mubarak s government in February 2011 in Egypt. The conclusion is that the phenomenon of the images on surfaces alters the perception of concepts that operate in the development of the science paradigms. At the same time, the phenomenon has influence in communication between men - our finding matches Ferrara s: in digital media, the possibility of communication is one of the possible variants, one that involves the senses of the human so as to produce movement (reaction)